2011
DOI: 10.1117/2.1201105.003720
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photoelectrochemical hydrogen production with swift heavy ion irradiation

Abstract: Conventional solar cells directly convert light to electricity. Alternatively, hydrogen production through splitting water in a photoelectrochemical cell has emerged as an advanced alternative to the conventional photovoltaic cell. The key limiting challenge in the process is to design a stable semiconductor electrode that, on exposure to sunlight, creates charge carriers that in turn produce hydrogen and oxygen. The primary requirements for suitable semiconductor photoelectrodes are sufficient solar-energy ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…There was no significant change in the Raman spectrum even after heating the sample up to a temperature of 450 °C, which indicates the stable microstructure of the tandem absorber. [43,44]. From the analysis of the Raman spectroscopy of the heat treated coating at 550 °C, it can be predicted that the heat treatment has introduced several modifications in the coating.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…There was no significant change in the Raman spectrum even after heating the sample up to a temperature of 450 °C, which indicates the stable microstructure of the tandem absorber. [43,44]. From the analysis of the Raman spectroscopy of the heat treated coating at 550 °C, it can be predicted that the heat treatment has introduced several modifications in the coating.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…[21][22][23][24][25][26] D. Avasthi et al 27 reported that when an energetic ion penetrates into any material, it loses energy mainly by two independent processes: (i) elastic collisions with the nuclei, known as nuclear energy loss (dE/dx)n, which dominates at an energy of about 1 keV per amu, and (ii) inelastic collisions of the highly charged projectile ion with the atomic electrons of the matter, known as electronic energy loss (dE/dx)e, which dominates at an energy of about 1 MeV per amu or more. Swi heavy ion irradiation (SHII) of nanostructures has induced changes in size and shape.…”
Section: Introductionmentioning
confidence: 99%
“…Swi heavy ions penetrate deep into the materials and generate a long and narrow disordered zone along the material's trajectory. [21][22][23][24][25][26] D. Avasthi et al 27 reported that when an energetic ion penetrates into any material, it loses energy mainly by two independent processes: (i) elastic collisions with the nuclei, known as nuclear energy loss (dE/dx)n, which dominates at an energy of about 1 keV per amu, and (ii) inelastic collisions of the highly charged projectile ion with the atomic electrons of the matter, known as electronic energy loss (dE/dx)e, which dominates at an energy of about 1 MeV per amu or more. In the inelastic collision (cross-section $ 10 À16 cm 2 ), the energy is transferred from the projectile to the atoms through excitation and ionization of the surrounding electrons.…”
Section: Introductionmentioning
confidence: 99%